Zamieszkanie Słowa Wcielonego - Pierzchała, Kazimierz (Collectanea Theologica, 2018)
The author’s views are founded on the thesis that the Prologue to the Fourth Gospel is based on an early Christian hymn from the second part of the 1st century, originating in the diaspora, interwoven with additions that connect it with the whole Gospel.